2022
DOI: 10.3390/foods11040527
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of TMA against Escherichia coli and Effect of Temperature and Storage Duration on TMA Content, Lysozyme Activity and Content in Eggs

Abstract: Studies on trimethylamine (TMA) in egg yolk have focused on how it impacts the flavor of eggs, but there has been little focus on its other functions. We designed an in vitro antibacterial test of TMA according to TMA concentrations that covered the TMA contents typically found in egg yolk. The change in TMA content in yolk was analyzed at different storage temperatures and for different storage durations. The known antibacterial components of eggs, including the cuticle quality of the eggshell and the lysozym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…We identified TMA in duck egg white and its egg yolk and found that TMA has an antibacterial effect in vitro. This is in accordance with earlier studies, which showed that TMA solutions reduce the survival of certain bacteria [ 81 , 82 ]. TMA, derived from the weak metabolic capability of FMO3, was deposited in the egg yolk and white of ducks.…”
Section: Discussionsupporting
confidence: 93%
“…We identified TMA in duck egg white and its egg yolk and found that TMA has an antibacterial effect in vitro. This is in accordance with earlier studies, which showed that TMA solutions reduce the survival of certain bacteria [ 81 , 82 ]. TMA, derived from the weak metabolic capability of FMO3, was deposited in the egg yolk and white of ducks.…”
Section: Discussionsupporting
confidence: 93%
“…TMA and benzoate induction of increased levels of ZO-1 was unexpected as both have been linked to inflammation in the gut (3739). Yet both molecules have antimicrobial properties and are toxic towards E. coli so it is possible that any positive effects on ZO-1 levels seen here were indirect due to the metabolites counteracting the negative effects of the bacterial supernatant treatment (40, 41). Interestingly, both 3,4-TMAB and 4-TMAP had similar effects at low concentrations, increasing ZO-1 levels.…”
Section: Discussionmentioning
confidence: 94%
“…The copyright holder for this preprint this version posted February 6, 2024. ; https://doi.org/10.1101/2024.02.06.579072 doi: bioRxiv preprint were indirect due to the metabolites counteracting the negative effects of the bacterial supernatant treatment (40,41). Interestingly, both 3,4-TMAB and 4-TMAP had similar effects at low concentrations, increasing ZO-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The main components of eggs include the albumen (57%), egg yolk (32%), eggshell (10%), and eggshell membrane (<1%) [11]. Due to their nutritional density, eggs have been hailed as an "ideal source of nutrition for humans [12]." Among these components, egg yolk offers various health benefits, such as preventing atherosclerosis, promoting the nervous system, bodily development, and enhancing metabolic and immune functions [13].…”
Section: Introductionmentioning
confidence: 99%